2021
DOI: 10.22270/ujpr.v6i4.633
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas Gingivalis: Biofilm Formation, Antimicrobial Susceptibility of Isolates From Cases of Localized Aggressive Periodontitis (Lap)

Abstract: Background: No information is available on the antimicrobial sensitivity pattern and guidelines for oral antibiotic therapy for Yemeni patients for those with localized aggressive periodontitis (LAP) due to Porphyromonas gingivalis, a condition that often requires complementary antibiotic treatment. Aim: The primary aim of the current study was to examine the antibiotic patterns and the potential relationship between P. gingivalis biofilm formation and the incidence of antibiotic resistance of clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the most important periodontal pathogens P. gingivalis appears to be one of the main etiological factors in the pathogenesis and development of inflammatory processes of periodontitis [ 46 ]. P. gingivalis expresses a wide array of virulence factors which include fimbriae, gingipains, collagenase, lipopolysaccharide, haemagglutinins, capsule, and superoxide dismutase [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on practically still limited information about the sensitivity of T. forsythia to various antimicrobial substances [ 54 ], our study also evaluated the antibacterial sensitivity of selected antibiotics. Amoxicillin-clavulanic acid, clindamycin, moxifloxacin, and metronidazole are among the most well-known drugs used as part of periodontal therapy in practice [ 46 ]. In this study, all T. forsythia isolates were sensitive to amoxicillin-clavulanic acid and moxifloxacin, while they showed resistance to metronidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation and survey of dental health problems in Yemen are in spite of everything fairly small and limited, even though there were studies that dealt with the problems of dental caries, the prevalence and pattern of third molar impaction in adults and children, periodontal infections, and causes of extraction of permanent teeth [1][2][3][4][5][6][7][8], however no exploration converge the prevalence of premature loss of primary teeth and its effect on malocclusion. Early loss of primary teeth is a worldwide problem.…”
Section: Introductionmentioning
confidence: 99%